Arahan Pengembangan Kawasan Sekitar Bandar Udara Internasional Sultan Hasanuddin Makassar - Irwan Irwan; Moh. Yoenus Osman; Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
Airport is one of important facility in increasing people’s mobility. It becomes a crucial support to the interregion movement and part of national transportation system’s aiding. Hence, the airport need some qualifications of development and exploitation, both in airport area and in safety of flight operational support area.The expansion of airport area that does not observe to the Guidelines for Airport Operational can cause the airplane accident. High density of settlement around the airport may blocking the radio waves which resulting in disfunction of radar and navigation tools. The developing of Sultan Hasanuddin International Airport of Makassar is a shape of realizing the inter-island, interregion, and international movement necessity. The development of airport area is occuring some impacts which has influence to the local inhabitance’s life and activities. On the contrary, the activities of local inhabitance will also occur some influences to the airport operational.This research is carried out by analizing some influences of airport existence to the surrounding area in the form of noise, safety area, flight operational, and Instrument Landing System area. The analysis of several above mentioned elements will resulting directive of expanding airport’s surrounding area within spatial planning exploitation and control.The method and analysis used at this research is Super Impose Analysis shaped by overlay, identify method, spatial join, and measuring impact based on both primary and secondary data obtained by circulate several questionnaires to local inhabitance that can find out some impacts they’ve been acquired from airport expansion area. The purpose of this research is detecting impact which occur at Sultan Hasanuddin International Airport of Makassar, in the case of its expansion surrounding area. Composing guidelines concept of the airport area development in order that negative impact can be minimized.